Risk Factors for Mortality in Neonatal Gastric Perforation: A Retrospective Cohort Study - Huang, Yao; Lu, Qi; Peng, Nan; Wang, Li; Song, Yan; Zhong, Qin; Yuan, Peng (Frontiers in Pediatrics, 2021)
Abstract Background: Neonatal gastric perforation is a rare but life-threatening issue. The aim of this study was to describe the clinical characteristics and prognosis of patients with neonatal gastric perforation and identify predictive factors for poor prognosis. Methods: This was a retrospective cohort study of patients with neonatal gastric perforation treated in a tertiary pediatric public hospital between April 2009 and October 2020. The enrolled patients were divided into survival and non-survival groups. Demographic information, clinical characteristics, laboratory and imaging features, and outcomes were collected from the electronic medical record. Univariate and multivariate logistic regression analyses were performed to obtain the independent factors associated with death risk. Additionally, we separated this population into two groups (preterm and term groups) and explored the mortality predictors of these two groups, respectively. Results: A total of 101 patients with neonatal gastric perforation were included in this study. The overall survival rate was 70.3%. Seventy-one (70.3%) were preterm neonates, and sixty-two (61.4%) were low-birth-weight neonates. The median age of onset was 3 days (range: 1-11 days). Abdominal distension (98 [97.0%] patients) was the most common symptom, followed by lethargy (78 [77.2%] patients), shortness of breath (60 [59.4%] patients) and vomiting (34 [33.7%] patients). Three independent mortality risk factors were identified: shock (OR,3.749; 95% CI, 1.247‒11.269; p= 0.019), serum lactic acid>2.5mmol/L (5.346; 1.727‒16.547; p=0.004) and platelet count <150× 10⁹/ L (3.510; 1.115-11.053; p=0.032). There was a borderline significant association between sclerema neonatorum and total mortality (4.827; 0.889‒26.220; p=0.068). In preterm infants, serum lactic acid>2.5mmol/L and platelet count <150× 10⁹/ L remained independent risk factors for death. In term infants, the incidence of shock, coagulopathy, pH<7.3, serum lactic acid>2.5mmol/L, and hyponatremia were statistically different between non-survival and survival groups. Conclusion: Shock, hyperlactatemia, and thrombocytopenia are independently associated with an increased risk of death in patients with neonatal gastric perforation. Identification of modifiable risk factors during the critical periods of life will contribute to the development of effective prevention and intervention strategies of neonatal gastric perforation.